Preparation and application of injectable bioadhesive hydrogel for endoscopic transnasal skull base dural sealing

CN122937276APending Publication Date: 2026-10-20HUAZHONG UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611093304.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-22
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0004]针对现有技术的以上缺陷或改进需求,本发明的目的在于提供一种用于内镜下经鼻颅底硬脑膜密封的可注射生物粘附水凝胶的制备与应用,与现有技术相比,本发明有效解决了预成型贴片难以经内镜狭窄通道输送,以及传统可注射水凝胶在倾斜缺损处易受重力流失的技术难题;同时克服了商业密封剂较弱湿粘附力的安全隐患

Benefits of technology

1、创新的“快/慢”双网络功能分工设计:由“快速”物理网络主导,完美兼顾微创注射与即刻原位停留。“快/慢”双网络交联机制为材料赋予了明确的功能分工(如后文图1所示)。在混合的初始阶段(如后文实施例1所示例的约3秒),海藻酸盐与钙离子快速形成的物理交联网络占据主导。该物理网络赋予了材料优异的剪切变稀特性,使其能够顺畅地通过长导管或穿刺针进行内镜下微创注射(如后文图2所示);同时,在剪切力消除后,其粘度能够瞬间恢复。与市售易受重力流失分散的可注射密封剂相比,本发明水凝胶在接触到呈90°甚至更具挑战性倾斜角度的颅底缺损表面时,能够实现即刻的界面停留与精准覆盖。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention belongs to the field of biomedical materials technology and discloses the preparation and application of an injectable bioadhesive hydrogel for endoscopic transnasal dura mater sealing. The precursors include a first solvent, a second solvent, alginate powder, calcium salt powder, amino-modified polyethylene glycol powder, and polyethylene glycol powder with active ester bonds. This enables: rapid ionic cross-linking of the alginate and calcium salt to form a first physical network; and slow covalent cross-linking of the amino-modified and active ester-modified polyethylene glycol to form a second chemical network. The first physical network and the second chemical network interpenetrate to form a dual-network system. This invention effectively solves the technical problems of pre-formed patches being difficult to deliver through narrow endoscopic channels and the susceptibility of traditional injectable hydrogels to gravity loss at tilted defects; it also overcomes the safety hazards of weak wet adhesion of commercial sealants.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of biomedical materials technology, and more specifically, relates to the preparation and application of an injectable bioadhesive hydrogel for endoscopic transnasal dura mater sealing. Background Technology

[0002] Endoscopic transnasal surgery is an important method for removing skull base tumors, but this procedure often results in dural defects lacking tissue support, leading to a very high risk of postoperative cerebrospinal fluid leakage, which can even be life-threatening. Due to the narrow and long surgical channel and limited field of vision in endoscopic surgery, traditional suturing techniques are difficult to implement. Therefore, clinicians rely heavily on commercially available sealants to establish a watertight barrier.

[0003] However, existing commercial sealants have significant limitations: for example, fibrin glue exhibits significantly reduced adhesion in moist environments rich in cerebrospinal fluid; and polyethylene glycol (PEG)-based sealants, such as DuraSeal, are prone to uncontrolled over-swelling under physiological conditions, posing a risk of nerve compression. In recent years, although novel hydrogel-based dura mater sealants have shown some performance improvements, they still face many limitations in practical clinical applications. Specifically, pre-formed hydrogel patches are difficult to deliver through narrow endoscopic channels; and traditional injectable hydrogels are prone to gravity-driven loss and dispersion at tilted defect interfaces, failing to achieve immediate defect coverage and resulting in unstable seals. Therefore, there is an urgent need to develop a novel dura mater sealant that combines minimally invasive injectability, interfacial retention capacity, strong wet interface adhesion, and long-term watertight stability. Summary of the Invention

[0004] In view of the above-mentioned defects or improvement needs of the prior art, the purpose of this invention is to provide an injectable bioadhesive hydrogel for endoscopic transnasal dura mater sealing. Compared with the prior art, this invention effectively solves the technical problems of pre-formed patches being difficult to deliver through the narrow channels of endoscopes and traditional injectable hydrogels being easily lost due to gravity at tilted defects; at the same time, it overcomes the safety hazards of the weak wet adhesion of commercial sealants.

[0005] To achieve the above objectives, according to a first aspect of the present invention, a precursor for an injectable bioadhesive hydrogel for endoscopic transnasal dura mater sealing is provided, comprising a first solvent, a second solvent, alginate powder, calcium salt powder, amino-modified polyethylene glycol powder, and polyethylene glycol powder modified with active ester bonds; wherein the first solvent is deionized water, and the second solvent is phosphate buffered saline (PBS). By mixing calcium salt powder with a first solvent to form a homogeneous solution containing calcium salt, mixing alginate powder with a second solvent to form a homogeneous solution containing alginate, and then mixing the homogeneous solution containing calcium salt with amino-modified polyethylene glycol powder to form a homogeneous first-component precursor solution, and finally mixing the homogeneous solution containing alginate with the polyethylene glycol powder modified with active ester bonds to form a homogeneous second-component precursor solution, the mixing of the first-component precursor solution and the second-component precursor solution can achieve the following: the alginate component and the calcium salt undergo rapid ionic cross-linking to form a first physical network, while the amino-modified polyethylene glycol component and the polyethylene glycol component modified with active ester bonds undergo slow covalent cross-linking to form a second chemical network. The first physical network and the second chemical network interpenetrate to form a dual-network system, which is an injectable and adhesive hydrogel.

[0006] According to a second aspect of the present invention, a precursor for an injectable bioadhesive hydrogel for endoscopic transnasal dura mater sealing is provided, comprising: a homogeneous solution containing calcium salts, a homogeneous solution containing alginate components, an amino-modified polyethylene glycol powder, and an amino-modified polyethylene glycol powder with active ester bonds; wherein the homogeneous solution containing calcium salts is in deionized water as a solvent, and the homogeneous solution containing alginate components is in phosphate-buffered saline (PBS) as a solvent. By separately mixing the homogeneous solution containing calcium salt and the amino-modified polyethylene glycol powder to form a homogeneous first-component precursor solution, and then mixing the homogeneous solution containing alginate and the active ester-modified polyethylene glycol powder to form a homogeneous second-component precursor solution, and finally mixing the first-component precursor solution and the second-component precursor solution, the following can be achieved: the alginate component and the calcium salt undergo rapid ionic cross-linking to form a first physical network, while the amino-modified polyethylene glycol component and the active ester-modified polyethylene glycol component undergo slow covalent cross-linking to form a second chemical network. The first physical network and the second chemical network interpenetrate to form a dual-network system, which is an injectable and adhesive hydrogel.

[0007] According to a third aspect of the invention, a two-component precursor solution for an injectable bioadhesive hydrogel for endoscopic transnasal dura mater sealing is provided, comprising a first-component precursor solution and a second-component precursor solution, wherein... The first component precursor solution is a homogeneous solution containing both calcium salt and amino-modified polyethylene glycol components. The second component precursor solution is a homogeneous solution containing both alginate components and polyethylene glycol components modified with active ester bonds. When the first component precursor solution and the second component precursor solution are mixed, the following can be achieved: the alginate component and the calcium salt undergo rapid ionic cross-linking to form a first physical network, while the amino-modified polyethylene glycol component and the active ester-modified polyethylene glycol component undergo slow covalent cross-linking to form a second chemical network. The first physical network and the second chemical network interpenetrate to form a dual-network system, which is an injectable and adhesive hydrogel.

[0008] As a further preferred embodiment of the present invention, the alginate component is selected from alginate and its derivatives, preferably selected from at least one of alginate, oxidized alginate, methacrylated alginate, and oxidized methacrylated alginate; The calcium salt is selected from at least one of calcium chloride, calcium sulfate, calcium carbonate, calcium lactate, calcium gluconate, and calcium hydrogen phosphate, preferably calcium sulfate or calcium carbonate.

[0009] As a further preferred embodiment of the present invention, the amino-modified polyethylene glycol component includes at least one of linear, biarm, triarm, tetraarm, hexaarm, or octaarm polyethylene glycols containing an amino group (-NH2). Preferably, the molecular weight of the amino-modified polyethylene glycol component is in the range of 2,000 to 40,000 Da.

[0010] As a further preferred embodiment of the present invention, the polyethylene glycol component modified with active ester bonds includes at least one of linear, biarmed, triarmed, tetraarmed, hexaarmed, or octaarmed polyethylene glycols containing N-hydroxysuccinimide (NHS) active end groups. Preferably, the active ester bond type includes one of succinimide glutarate (SG), succinimide succinate (SS), succinimide propionate (SAP), and succinimide azelate (SAZ); More preferably, the polyethylene glycol component modified with active ester bonds has a molecular weight range of 2,000 to 40,000 Da.

[0011] As a further preferred embodiment of the present invention, in the first component precursor solution, the mass ratio of calcium salt to solvent volume is 0.0005 g / mL to 0.005 g / mL, preferably 0.001 g / mL to 0.0015 g / mL; In the second component precursor solution, the mass ratio of alginate to solvent volume is 0.005 g / mL to 0.05 g / mL, preferably 0.01 g / mL to 0.015 g / mL; The amino-modified polyethylene glycol component contained in the first component precursor solution and the polyethylene glycol component with active ester bond modification contained in the second component precursor solution satisfy the following: the molar ratio of amino (-NH2) functional group to active ester bond (-NHS) functional group is 1:0.5 to 1:5, preferably 1:1.5.

[0012] According to a fourth aspect of the present invention, the present invention provides a method for preparing the above-mentioned two-component precursor solution, comprising the following steps: Preparation steps of the first component precursor solution: Dissolve the amino-modified polyethylene glycol component powder in a pre-prepared calcium salt aqueous solution, mix evenly to obtain the first component precursor solution; Preparation steps of the second component precursor solution: Dissolve the polyethylene glycol component powder with active ester bond modification in pre-prepared phosphate buffer (PBS) containing alginate, and mix well to obtain the second component precursor solution.

[0013] According to a fifth aspect of the present invention, the present invention provides the use of the above-mentioned precursor or the above-mentioned two-component precursor solution in the preparation of dura mater sealant.

[0014] According to a sixth aspect of the present invention, the present invention provides an injectable bioadhesive hydrogel for endoscopic transnasal dural sealing of the skull base. The hydrogel is obtained by rapidly injecting the above-mentioned two-component precursor solution into the target defect area to be repaired in the dural base of the skull base after mixing, and then curing it in situ. It can be used as a dural sealant. The in-situ curing is carried out at 25℃~37℃; The first component precursor solution and the second component precursor solution are respectively placed in the two syringes of a double-barrel syringe, which is a Luer head connected syringe.

[0015] Compared with existing technologies, the technical solution conceived in this invention optimizes the composition of the hydrogel by utilizing alginate components, calcium salt crosslinking agents, and polyethylene glycol components with different modified groups (i.e., polyethylene glycol with amino modifications and polyethylene glycol with active ester bonds). This constructs an innovative "fast / slow" dual-network crosslinking system, which is an injectable bioadhesive hydrogel suitable for endoscopic transnasal dura mater sealing. This "fast / slow" design endows the two networks with synergistic and differentiated functions: the rapidly forming physical crosslinking network imparts shear-thinning properties to the material, enabling minimally invasive injection and immediate in-situ retention; while the slow covalent crosslinking network provides mechanical self-reinforcement and long-lasting tissue interface anchoring. This hydrogel combines minimally invasive injectability, immediate in-situ interface retention capability, strong tissue adhesion, and good mechanical stability, enabling complete coverage and fitting of irregular defects, achieving long-term watertight sealing of complex tilted dura mater defects.

[0016] Considering various practical needs, the injectable bioadhesive hydrogel for endoscopic transnasal skull base dura mater sealing of this invention can be in the form of a final hydrogel, or in the form of a two-component precursor solution (two separate precursor solutions) or a precursor (multiple materials separate, or some materials premixed). Taking the application of the two-component precursor solution as an example, by mixing the two-component precursor solutions, in the initial stage after mixing, the physical cross-linking network rapidly formed by alginate and calcium ions dominates, giving the material excellent injectability due to shear thinning and the ability to remain at the interface in situ on the inclined tissue surface; subsequently, the slow covalent cross-linking of the two polyethylene glycol components gradually dominates, enabling the material to achieve self-reinforcement of mechanical properties in situ and form a firm interface anchor with the tissue surface. Furthermore, unlike existing technologies that artificially achieve fast-slow dual-network structures through additional excitation methods (e.g., artificially controlling the introduction of photoexcitation or thermal excitation at a certain point in time to achieve a phased fast-slow network), this invention utilizes alginate components, calcium salt crosslinking agents, amino-modified polyethylene glycol, and polyethylene glycol modified with active ester bonds to spontaneously construct a fast-slow dual-network crosslinking system through the interactions between the components. Crosslinking can be carried out uniformly within the range of room temperature (25°C) to physiological temperature (37°C), making the process convenient.

[0017] Specifically, the present invention can achieve the following beneficial effects: 1. Innovative "Fast / Slow" Dual-Network Functional Division Design: Dominated by the "fast" physical network, it perfectly balances minimally invasive injection and immediate in-situ placement. The "fast / slow" dual-network cross-linking mechanism endows the material with a clear functional division (as described below). Figure 1As shown). In the initial stage of mixing (approximately 3 seconds, as illustrated in Example 1 below), the rapidly formed physical cross-linked network of alginate and calcium ions dominates. This physical network endows the material with excellent shear-thinning properties, enabling smooth endoscopic minimally invasive injection through long catheters or puncture needles (as shown below). Figure 2 (As shown); simultaneously, its viscosity can be instantly restored after the shear force is eliminated. Compared with commercially available injectable sealants that are easily dispersed by gravity, the hydrogel of this invention can achieve immediate interfacial retention and precise coverage when in contact with skull base defects at 90° or even more challenging tilt angles.

[0018] 2. A long-lasting and stable watertight barrier is constructed through in-situ mechanical self-reinforcement and persistent tissue anchoring dominated by a "slow" covalent network. Based on the in-situ retention achieved by the physical network, the slow covalent cross-linking between the two types of polyethylene glycol components gradually becomes dominant (completed within approximately 30 minutes, as illustrated in Example 1 below). The formation of the covalent network not only enables the material to achieve in-situ mechanical self-reinforcement, but its free active ester bonds can also covalently bind with amino groups on the tissue surface, forming a strong interfacial anchor. As illustrated in Example 1 below, the hydrogel obtained in Example 1 can withstand an in vitro burst pressure of 67.4 mmHg after 5 minutes, and a fully cured pressure of 251.6 mmHg after 30 minutes, far exceeding the normal cerebrospinal fluid pressure, and can withstand the transient intracranial hypertension impact (approximately 75 mmHg) caused by postoperative coughing or sneezing. More importantly, this invention effectively overcomes the clinical defect of commercially available dura mater sealants being prone to excessive swelling by optimizing the network structure. The hydrogel exhibits low swelling characteristics (approximately 40%, as exemplified by the sample in Example 1 below), and its burst pressure remains above 200 mmHg after immersion in a simulated in vivo physiological environment for 24 hours (as exemplified by the sample in Example 1 below). Furthermore, thanks to the energy dissipation mechanism of reversible breaking and recombination of dynamic ionic bonds, the prepared hydrogel can still rapidly recover its initial shape without significant peak stress decay after being subjected to continuous cyclic compression at 70% high strain, exhibiting excellent fatigue resistance and adapting to the dynamic deformation of dura mater tissue (as exemplified by the sample in Example 1 below).

[0019] 3. The procedure is simple to perform clinically and possesses extremely high translational potential. The raw materials are safe and have excellent biocompatibility. In clinical applications, the hydrogel of this invention provides doctors with a simple "single-step application" strategy. This invention can be particularly applied in the form of a two-component precursor solution. Uniform mixing and direct in-situ injection of the precursor can be achieved by repeatedly injecting it back and forth with a double-barrel syringe (approximately 3 seconds as illustrated in Example 1 below), without any additional procedures. This design greatly simplifies the surgical procedure. Furthermore, the hydrogel obtained based on this invention does not cause significant inflammation or foreign body reactions. Moreover, this hydrogel provides a solid physical barrier in the critical early stages of dura mater healing, and is gradually degraded and absorbed as new tissue grows, eliminating the burden of secondary surgical removal.

[0020] For transnasal skull base dura mater sealants, achieving both "minimally invasive injection" and "gravity-resistant in-situ retention" is often difficult in clinical practice. Single cross-linking presents a significant time-dynamic bottleneck: excessively rapid cross-linking prematurely disrupts shear-thinning properties, leading to injection device blockage; excessively slow cross-linking results in premature dilution by cerebrospinal fluid before formation, causing complete seal failure. To address this, this invention creatively designs a time-scale decoupled "fast / slow dual-network" mechanism, achieving a perfect balance between injectability and dwell time at the tilted interface. Combined with subsequent mechanical self-reinforcement, this successfully achieves a near-ideal dura mater sealant.

[0021] In summary, compared with existing technologies, this invention, through innovative component design and a "fast / slow" dual-network cross-linking mechanism, successfully overcomes the clinical technical bottlenecks of pre-formed patches being difficult to deliver endoscopically and traditional injectable hydrogels being prone to leakage on sloping wounds. The resulting hydrogel combines convenient injection, spatial stability, strong wet surface adhesion, and resistance to dynamic fatigue, effectively solving the pain points of dural defect reconstruction in endoscopic transnasal skull base surgery. It has a leak-proof sealing function, is suitable for minimally invasive surgery, and has extremely important clinical application value and translational prospects.

[0022] The precursor and two-component precursor solution obtained based on this invention combine the convenience of minimally invasive injection with the ability to remain at the tilted interface. Furthermore, after in-situ self-reinforcement, they exhibit low swelling, fatigue resistance, and high burst pressure, maintaining a long-term stable watertight seal under physiological conditions. This has significant clinical translational value in the field of minimally invasive reconstruction of complex dural defects. This invention effectively meets the growing translational demand for high-performance tissue sealing materials in minimally invasive surgery, providing a mechanism-driven strategy with great clinical translational potential for endoscopic transnasal skull base dural sealing. Attached Figure Description

[0023] Figure 1 This is a schematic diagram illustrating the principle of the "fast / slow" dual-network crosslinking mechanism of the hydrogel of the present invention and a schematic diagram showing the dynamic evolution of its modulus over time.

[0024] Figure 2 The letter pattern of CNAS in Embodiment 1 of the present invention is continuously extruded and formed by a 26G needle.

[0025] Figure 3 The results of rheological and crosslinking kinetic tests for each group of hydrogels (comparative Example 1: single-network CA; comparative Example 2: single-network NS; and Example 1: dual-network CNAS) are shown below; Figure 3 In the figure, 'a' represents the crosslinking kinetics test results of the evolution of the storage modulus (G') and loss modulus (G'') of each group of hydrogels over time (where the red dashed circle indicates the gelation critical point of the single-network NS hydrogel). Figure 3 In the figure, b is a comparison of the macroscopic morphology of CNAS in the initial gelation stage (i.e., the first stage) and after mechanical self-reinforcement (i.e., the second stage).

[0026] Figure 4 These are the results of in vitro swelling performance tests; among them, Figure 4 In the figure, 'a' represents the in vitro swelling behavior curves of each group of samples in PBS buffer at 37°C. Figure 4 Figure b shows a comparison of the macroscopic morphology of each group of materials before and after soaking in PBS buffer at 37°C for 24 hours (the black dashed circles in the figure indicate the boundaries of the hydrogel after swelling).

[0027] Figure 5 This diagram illustrates the tissue shear adhesion test and the test results; among them, Figure 5 In the diagram, 'a' represents a schematic diagram of a tissue overlap shear test. Figure 5 In the figure, b is a comparison of the shear adhesion strength of each group of samples on the surface of pig skin tissue.

[0028] Figure 6 This diagram illustrates the external burst pressure test and its results; among them, Figure 6 In the diagram, 'a' represents the experimental setup for the external burst pressure test. Figure 6 In the figure, b is a comparison of the in vitro burst pressure of each group of samples at different time points (the gray shaded area and the dashed line in the figure represent the fluctuation range of normal intracranial pressure and the peak value of transient intracranial pressure, respectively). Figure 6 In the figure, c represents the in vitro burst pressure comparison of the CNAS sample of Example 1 on day 3 and day 5.

[0029] Figure 7 The results are from the fatigue resistance test; among them, Figure 7 In the figure, 'a' is a comparison of the macroscopic morphology of each group of samples before and after continuous cyclic compression at 70% strain. Figure 7 In the figure, b represents the cyclic compressive stress-time curve of each group of samples.

[0030] Figure 8 These are the results of in vitro cell compatibility tests; among them, Figure 8Figure 'a' shows the results of live / dead fluorescence staining of NHA cells cultured in DMEM medium (control group) (green indicates live cells, red indicates dead cells; the same applies below). Figure 8 b in the figure shows the results of live / dead fluorescence staining of NHA cells cultured using CNAS extract; Figure 8 In the figure, c represents the quantitative statistical result of the number of viable cells after the two groups of NHA cells were cultured.

[0031] Figure 9 This diagram illustrates the endoscopic transnasal skull base dura mater interface dwell time test and its results; among which... Figure 9 In the diagram, 'a' represents the procedure for injecting material via the transsphenoidal approach under endoscopy. Figure 9 b, c, and d in the figure are representative images of the CNAS sample, the commercially available dura mater sealant sample, and the commercially available fibrin glue sample injected in situ into the tilted defect, respectively (the dashed lines in the figure indicate the actual distribution range of each sample). Detailed Implementation

[0032] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention. Furthermore, the technical features involved in the various embodiments of this invention described below can be combined with each other as long as they do not conflict with each other.

[0033] Unless otherwise explicitly stated, the concentrations of each component appearing in the following examples and comparative examples refer to the mass-volume concentration (w / v; where w represents the mass of the corresponding solute and v represents the volume of the solvent; similar to conventional methods, 1% mass-volume concentration = 0.01 kg / L = 0.01 g / mL); the specific amounts of each raw material weighed during the preparation process are calculated based on the concentration before mixing and the required volume of the precursor solution.

[0034] Taking sodium alginate (SA), calcium sulfate (CaSO4), four-arm polyethylene glycolamine (4-arm PEG-NH2, Mn = 10 kDa), and four-arm polyethylene glycol succinimide glutarate (4-arm PEG-SG, Mn = 10 kDa) as examples, the preparation method of the dura mater sealant includes the following steps: 1. Preparation of two-component precursor solution: Component 1: At room temperature, add 0.05% to 0.5% (especially 0.1% to 0.15%) of CaSO4 to deionized water and stir magnetically until completely dissolved; then add 3% to 5% of 4-arm PEG-NH2 (stored in a -20°C refrigerator before use) and continue stirring until a homogeneous solution is formed.

[0035] Component 2: At room temperature, add 0.5% to 5.0% (especially 1% to 1.5%) of SA to PBS buffer and stir magnetically until completely dissolved; then add 4.5% to 7.5% of 4-arm PEG-SG (with active ester bonds; store at -20°C before use) and continue stirring until a homogeneous solution is formed.

[0036] 2. Mixing and curing of precursors into a gel: Load the prepared components one and two into syringes (prepare fresh each time), connect the syringes via Luer nozzles, and rapidly shear-mix the two components at a 1:1 (v / v) volume ratio, injecting back and forth three times to ensure thorough homogenization of the system. During the mixing process, a physical network is rapidly formed, followed by slow covalent cross-linking that self-reinforces the material in situ into a stable sealing barrier.

[0037] The following are specific examples: Implementation Case 1 The preparation method of the dura mater sealant in this implementation case is as follows: 1. Preparation of two-component precursor solution: Component 1: At room temperature, add 0.15% CaSO4 to deionized water and stir magnetically until completely dissolved; then add 4% 4-arm PEG-NH2 (Mn = 10 kDa) and continue stirring until a homogeneous solution is formed.

[0038] Component 2: At room temperature, add 1.5% SA to PBS buffer and stir magnetically until completely dissolved; then add 6% 4-arm PEG-SG (Mn = 10 kDa) and continue stirring until a homogeneous solution is formed.

[0039] The molar ratio of amino (-NH2) functional groups to active ester (-NHS) functional groups is 1:1.5.

[0040] 2. Mixing and curing of precursors into a gel: The prepared components one and two were loaded into syringes, which were then connected via Luer nozzles. The two components were rapidly sheared and mixed at a 1:1 (v / v) volume ratio, with three back-and-forth injections to ensure complete homogenization of the system. During the approximately 3-second mixing process, a physical network was rapidly formed, followed by slow covalent cross-linking, which within 30 minutes transformed the material into a stable, self-reinforcing sealing barrier in situ.

[0041] The dura mater sealant in Implementation Case 1 is CNAS.

[0042] In addition, the system after being mixed thoroughly by three back-and-forth injections in step 2 of Example 1 is continuously extruded and shaped using a 26G needle, such as... Figure 2 As shown, the macroscopic size and shape of the CNAS prepared in Example 1 can be flexibly adjusted.

[0043] Implementation Case 2 The preparation method of the dura mater sealant in this implementation case is as follows: 1. Preparation of two-component precursor solution: Component 1: At room temperature, add 0.1% CaSO4 to deionized water and stir magnetically until completely dissolved; then add 3% 4-arm PEG-NH2 (Mn = 10 kDa) and continue stirring until a homogeneous solution is formed.

[0044] Component 2: At room temperature, add 1.0% SA to PBS buffer and stir magnetically until completely dissolved; then add 4.5% 4-arm PEG-SG (Mn = 10 kDa) and continue stirring until a homogeneous solution is formed.

[0045] The molar ratio of amino (-NH2) functional groups to active ester (-NHS) functional groups is 1:1.5.

[0046] 2. Mixing and curing of precursors into a gel: Load the prepared components one and two into syringes respectively, connect the syringes through Luer heads, and rapidly shear and mix the two components at a volume ratio of 1:1 (v / v).

[0047] Performance Evaluation: After mixing the two components, the low concentrations of alginate and calcium ions still rapidly form a physical cross-linked network, imparting shear-thinning properties to the system to maintain injectability. In the subsequent slow covalent cross-linking stage, due to the low concentration of the polyethylene glycol precursor, the gelation time is relatively long (approximately 116.7 s). This formulation ultimately achieves in-situ self-reinforcing formation of a stable sealing barrier, but the time required to reach complete curing is longer than in Example 1, making it suitable for clinical scenarios with longer operating time windows.

[0048] Implementation Case 3 The preparation method of the dura mater sealant in this implementation case is as follows: 1. Preparation of two-component precursor solution: Component 1: At room temperature, add 0.15% CaSO4 to deionized water and stir magnetically until completely dissolved; then add 5% 4-arm PEG-NH2 (Mn = 10 kDa) and continue stirring until a homogeneous solution is formed.

[0049] Component 2: At room temperature, add 1.5% SA to PBS buffer and stir magnetically until completely dissolved; then add 7.5% 4-arm PEG-SG (Mn = 10 kDa) and continue stirring until a homogeneous solution is formed.

[0050] The molar ratio of amino (-NH2) functional groups to active ester (-NHS) functional groups is 1:1.5.

[0051] 2. Mixing and curing of precursors into a gel: Load the prepared components one and two into syringes respectively, connect the syringes through Luer heads, and rapidly shear and mix the two components at a volume ratio of 1:1 (v / v).

[0052] Performance Evaluation: At this formulation, alginate and calcium ions rapidly form a dense physical network, providing excellent initial interface retention. During the slow covalent crosslinking stage, the high concentration of polyethylene glycol precursor promotes rapid covalent network formation, significantly shortening the gel time (approximately 16.7 s). This formulation can rapidly form a high-strength watertight barrier, making it suitable for demanding defect repair scenarios involving instantaneous high-pressure cerebrospinal fluid leakage and requiring rapid self-reinforcement to resist fluid erosion. Furthermore, due to rapid curing, the thrust increases quickly during injection.

[0053] Comparison Case 1 This comparative case is an ionically cross-linked hydrogel. The preparation method is as follows: 1. Preparation of two-component precursor solution: Component 1: At room temperature, add 0.15% CaSO4 to deionized water and stir magnetically until completely dissolved.

[0054] Component 2: At room temperature, add 1.5% SA to PBS buffer and stir magnetically until completely dissolved.

[0055] 2. Mixing and curing of precursors into a gel: Using the same dual-barrel syringe shear mixing method as in Example 1, the two components were rapidly sheared and mixed into a gel at a volume ratio of 1:1 (v / v).

[0056] Let CA be the hydrogel in Comparative Case 1.

[0057] Comparison Case 2 This comparative case is a covalently chemically cross-linked hydrogel. The preparation method is as follows: 1. Preparation of two-component precursor solution: Component 1: At room temperature, add 4% of 4-arm PEG-NH2 (Mn = 10 kDa) to deionized water and stir magnetically until completely dissolved.

[0058] Component 2: At room temperature, add 6% of 4-arm PEG-SG (Mn = 10 kDa) to PBS buffer and stir magnetically until completely dissolved.

[0059] 2. Mixing and curing of precursors into a gel: Using the same dual-barrel syringe shear mixing method as in Example 1, the two components were rapidly sheared and mixed into a gel at a volume ratio of 1:1 (v / v).

[0060] Let the hydrogel in Comparative Case 2 be NS.

[0061] In addition, commercially available medical fibrin glue and commercially available dura mater sealant were used as control samples. The commercially available medical fibrin glue was purchased from Guangzhou Beixiu Biotechnology Co., Ltd. (trade name: Beixiu Glue); the commercially available dura mater sealant was purchased from Shandong Saikesaisi Biotechnology Co., Ltd. (trade name: Sainaoning). In all comparative experiments, the above two commercially available control samples were prepared and used strictly according to the product instructions provided by the manufacturers. The present invention conducted simultaneous performance tests and comparisons on the above-mentioned commercially available control samples and the samples prepared in Example 1, Comparative Example 1, and Comparative Example 2.

[0062] Performance testing: Rheological and crosslinking kinetic tests: The crosslinking kinetics of the hydrogel system were characterized using a rotational rheometer (MCR 102, Anton Paar) equipped with a 20 mm parallel plate test fixture at a physiological temperature of 37°C. The specific implementation scheme is as follows: i. Sample addition and preparation: The two-component precursor solutions of the dura mater sealant (CNAS group) of Example 1 and the comparative single-network hydrogels (CA group, NS group) were rapidly mixed and extruded onto the isothermal testing platform of the rheometer. The parallel plate was then quickly lowered to the set testing gap. The entire sample addition and preparation time was strictly controlled to approximately 15 seconds. ii. Time-scan test: The rheological test parameters were set to a constant strain of 1% and a constant frequency of 1 Hz. Under these conditions, a continuous time-scan test was performed on the above samples for 30 minutes. iii. Data Recording and Analysis: The testing instrument records the data on the evolution of the storage modulus (G') and loss modulus (G'') of each group of hydrogels over time throughout the entire process. Subsequently, the modulus-time curves of the samples are output using Origin plotting software.

[0063] The results are as follows Figure 3 As shown. (Through) Figure 3 As can be seen from 'a' in Example 1 of this invention, the "fast / slow" dual-network crosslinking mechanism is analyzed as follows: Due to the approximately 15 s sample addition and gap adjustment time before the rheometer test, the CA group of Comparative Example 1 did not show the intersection of G' and G''. However, it exhibited a stable G' value in the initial stage of the test, indicating that the physical crosslinking network of alginate and calcium ions rapidly gelled and reached stability in a very short time. In contrast, the G' / G'' intersection of the NS group of Comparative Example 2 appeared at 30 s after the start of the test. Adding this to the 15 s instrument adjustment time, its actual gelation time was approximately 45 s. Subsequently, the G' of the NS hydrogel rapidly increased and reached the rheological plateau at approximately 30 min, indicating that the polyethylene glycol covalent network had basically completed crosslinking. For the CNAS of Example 1 of this invention, its rheological evolution trajectory perfectly combines the instantaneous gelation of CA and the slow reinforcing characteristics of NS. Following mixing of the two-component precursors, CNAS rapidly established its initial modulus (G' = 46.7 Pa) due to the rapid formation of the physical network. Within the next 30 minutes, as the covalent network gradually formed, G' exhibited an exponential increase, increasing nearly 100-fold, ultimately reaching a high modulus of 4648.8 Pa. This mechanical strengthening could also be observed macroscopically, such as... Figure 3 As shown in b: Initially (e.g., 0 seconds after the start of the test), CNAS is soft and difficult to grasp with tweezers, but over time, the self-reinforcing network makes CNAS easier to grasp (e.g., 30 minutes after the start of the test).

[0064] In vitro swelling performance test: First, accurately weigh and record the initial wet weight of each group of test samples (i.e., CNAS, commercially available fibrin glue, and commercially available dura mater sealant; each group of test samples was the sample after gel stabilization for 30 min), denoted as W0; then, completely immerse each group of samples in PBS buffer (in petri dishes) and place them in a constant temperature track shaker at 37°C and 50 rpm; remove the samples at 3, 6, 12, 18, and 24 hours of immersion, gently blot dry the surface moisture with filter paper, and weigh them. The real-time wet weight of the samples at each time point is recorded as W0. tThe macroscopic volume changes of each group of samples were photographed and recorded after immersion in PBS at 37°C for 24 hours. The swelling ratio of each group of samples was calculated using the following formula:

[0065] Macroscopic immersion experiment and quantitative analysis results are as follows Figure 4 As shown, under the same simulated physiological environment, the commercially available dura mater sealant experienced uncontrollable excessive swelling, with a 24-hour swelling rate as high as 246.4 ± 7.5%; in contrast, the swelling rate of the commercially available fibrin glue was 2.9 ± 0.9%; and the swelling rate of the CNAS hydrogel in Example 1 of this invention was 39.9 ± 1.8%. The controllable low swelling characteristics exhibited by the hydrogel of this invention not only reduce the safety risks of brain nerve compression, but more importantly, provide an important guarantee for the hydrogel to maintain a long-term stable watertight seal in a moist physiological environment rich in cerebrospinal fluid.

[0066] Tissue shear adhesion test: The interfacial adhesion strength of the sample to the isolated tissue was quantitatively characterized by an overlap shear test. The specific test procedure is as follows: Fresh isolated pigskin was fixed onto a polyethylene terephthalate (PET) film using cyanoacrylate adhesive (Krazy glue, Toagosei) as the test substrate. CNAS-grade adhesive, commercially available medical fibrin glue, and commercially available dura mater sealant from Example 1 of this invention were injected in situ into the overlapping area of ​​two pieces of pigskin (overlap size 1.5 cm × 1.5 cm). PBS buffer solution was pre-dropped onto the surface of the pigskin to simulate a humid environment. A constant weight of 20 g was applied above the overlapping area. The mixture was then crosslinked and cured at 37°C for 30 min. A peel test was performed using a universal testing machine at a constant tensile rate of 2 mm / min, and the maximum shear force was recorded.

[0067] Shear strength is calculated using the following formula:

[0068] Where F max A and B represent the maximum shear force during debonding and the contact area of ​​the adhesive interface, respectively.

[0069] Because pigskin is highly similar to human tissue in biological characteristics, it was chosen as a test substrate for evaluating adhesion strength.

[0070] Quantitative test results as follows Figure 5As shown in b, the shear adhesion strength of CNAS reaches 32.4 ± 3.9 kPa, which is significantly better than that of commercially available dura mater sealants (14.5 ± 3.3 kPa) and commercially available fibrin glue (2.6 ± 1.5 kPa). This indicates that the hydrogel of the present invention has strong tissue adhesion ability and can effectively overcome the disadvantage of commercial sealants having severely reduced adhesion in moist environments such as cerebrospinal fluid.

[0071] External burst pressure test: A customized burst pressure testing mold was used to quantitatively evaluate the sealing ability of each group of samples after short-term curing and long-term immersion in a physiological environment. The specific testing procedure is as follows: A circular defect with a diameter of 3 mm was created in the center of the isolated fascia tissue using a biopsy punch. The CNAS of this invention, commercially available medical fibrin glue, and commercially available dura mater sealant were injected in situ into the moistened defect (the moistening treatment involved pre-dripping PBS buffer solution onto the fascia tissue), and the sample coverage was restricted to a circular area with a diameter of 10 mm centered on the defect using the mold. For samples of different testing periods, the following treatments were performed: Short-term curing group: The samples were placed in a humid environment at 37°C for cross-linking curing for 5 min and 30 min, respectively. Long-term stability evaluation group: The samples were placed in a humid environment at 37°C for cross-linking curing for 30 min, and then immersed in PBS buffer at 37°C for 24 hours, 3 days, and 5 days. Tissue was fixed onto a custom-designed burst pressure test mold, and PBS buffer was continuously injected into the chamber at a constant rate of 2 mL / min using a syringe pump (ISPLab02, DK INFUSETEK). Pressure changes within the chamber were continuously monitored and recorded using a digital manometer (GM520, Benetech). During continuous pressurization, the highest peak pressure recorded by the instrument when the adhesion between the sealing material and the tissue interface fails, or when the sealing material itself ruptures, causing a momentary leak, is the burst pressure of the sample.

[0072] Burst pressure is a key clinical indicator for assessing the ability of sealing materials to resist intracranial pressure fluctuations and maintain long-term barrier function. Results are as follows: Figure 6As shown in b, CNAS's sealing performance at various time points perfectly meets stringent clinical requirements. Firstly, after only 5 minutes of in-situ cross-linking in a simulated humid environment at 37°C, the burst pressure of CNAS reached 67.4 ± 14.9 mmHg. This value far exceeds the normal range of intracranial pressure fluctuations (6–13 mmHg), indicating that it provides immediate leak-proof protection for the defect area in the early stages. Subsequently, thanks to the mechanical self-reinforcement of slow covalent cross-linking, the burst pressure of CNAS increased to 251.6 ± 22.2 mmHg after 30 minutes of curing, sufficient to withstand the instantaneous increase in intracranial pressure (75 mmHg) caused by postoperative sneezing or coughing.

[0073] More importantly, thanks to its controllable low swelling properties, CNAS maintained a high burst pressure of over 200 mmHg after 24 hours of immersion, significantly outperforming commercially available products. In contrast, commercially available dura mater sealants experienced uncontrollable volume expansion during immersion, resulting in a decrease in burst pressure from 74.3 ± 9.6 mmHg to 6.5 ± 0.9 mmHg, rendering them ineffective as a sealing barrier in the face of normal physiological pressure fluctuations.

[0074] Furthermore, on days 3 and 5 in the simulated in vivo environment, CNAS still maintained a high burst pressure of over 200 mmHg, further demonstrating its long-term stability.

[0075] Fatigue resistance test: The fatigue resistance and structural stability of each group of samples were evaluated using cyclic compression tests. The specific test procedure is as follows: The CNAS-certified compound from Example 1 of this invention, commercially available medical fibrin glue, and commercially available dura mater sealant were injected in situ into custom molds to prepare cylindrical standard test samples with a diameter of 10 mm and a height of 5 mm. Subsequently, all samples were placed at 37°C for 1 hour to ensure complete cross-linking and curing. At room temperature, cyclic loading-unloading tests were performed on each group of samples using a universal testing machine. The constant speed of the instrument was set to 2.5 mm / min, and the maximum compressive strain was set to 70%. Five complete compression-unloading cycles were performed on each group of samples, and the stress-strain curves during the cycles were monitored and recorded. Simultaneously, the macroscopic structural integrity of each group of samples was recorded using a camera at the initial state, after being compressed to 70% deformation, and after five complete cycles.

[0076] In practical clinical applications, in order to withstand the dynamic tissue deformation of the human body and the periodic fluctuations in intracranial pressure, sealing materials must possess excellent mechanical toughness and fatigue resistance. Combined with... Figure 7The macroscopic test results in section 'a' show that, under continuous cyclic compression testing at 70% of maximum strain, both commercially available fibrin glue and commercially available dura mater sealant experienced irreversible structural collapse or complete rupture. In stark contrast, the CNAS of Example 1 of this invention, after undergoing cyclic compression of the same intensity, was able to rapidly recover to its initial shape without structural damage. Furthermore, the CNAS did not exhibit significant peak stress decay, confirming its fatigue resistance properties (e.g., ...). Figure 7 (As shown in b) From a microscopic mechanism perspective, this is attributed to the synergistic effect of the "physical-chemical" dual-network structure designed in this invention: the dynamic ionic bonds formed by alginate and calcium ions can effectively dissipate externally applied mechanical energy through reversible breakage and recombination when the material undergoes large strain; simultaneously, the covalent network formed by the cross-linking of polyethylene glycol components serves as a robust underlying framework, maintaining the overall structural integrity of the material. This energy dissipation mechanism and fatigue resistance provide a solid mechanical basis for the hydrogel of this invention to function as a watertight barrier stably and for a long time in complex dynamic physiological environments.

[0077] In vitro cell compatibility test: Good biocompatibility is a key prerequisite for the clinical application of materials. This invention uses a live / dead cell dual staining method to evaluate the in vitro cytotoxicity of samples. The specific test protocol is as follows: Human astrocytes (NHA) were seeded and cultured in 24-well plates. Simultaneously, the CNAS hydrogel sample obtained in Example 1 was immersed in DMEM medium for 24 hours, then the hydrogel was removed, and the liquid was collected to obtain the CNAS extract. Subsequently, the cells were treated and co-incubated for 24 hours using the CNAS extract (conditioned medium) from Example 1 of this invention and DMEM medium (blank control group), respectively. After co-incubation, the cells were stained for 30 minutes using a mixed staining solution of calcein-AM (for labeling live cells to emit green light) and propidium iodide (for labeling dead cells to emit red light). After washing, the cell viability was observed and images were acquired under a fluorescence microscope (Olympus IX71); and the area and number of live cells were quantitatively analyzed using ImageJ image processing software.

[0078] Combination Figure 8 Fluorescence images and quantitative data showed that almost all NHA cells exhibited green fluorescence signals 24 hours after treatment with the extract. Quantitative analysis further confirmed that the number of viable cells in the hydrogel extract-treated group was not significantly different from that in the blank control group treated with DMEM, demonstrating good cell compatibility and meeting the stringent safety requirements for clinical materials, without causing significant inflammation or foreign body reactions.

[0079] Endoscopic transnasal skull base dura mater interface dwell test: Using cadaveric human head specimens, the interfacial retention capacity of each group of samples was further evaluated under a simulated clinical minimally invasive surgical environment. The specific test protocol is as follows: Frozen cadaveric human head specimens were used as test models (the acquisition and experimental procedures of these specimens had undergone rigorous review and approval by the relevant medical ethics committee, ethics approval number 2025-S151). A standard endoscopic transsphenoidal approach was performed by a professional physician using a neuroendoscopic system (KARL STORZ, TC200). Under real-time endoscopic guidance, surgical instruments were inserted through the nasal cavity, exposing the middle turbinate and successfully entering the sphenoid sinus opening. Subsequently, a micro-drill was used to sequentially remove the anterior wall of the sphenoid sinus, the septum, and the sella turcica. After fully exposing the target area dura mater, a skull base dura mater defect of approximately 1 cm in diameter was artificially created to simulate cerebrospinal fluid leakage during clinical surgery. Under endoscopic guidance, each group of samples was injected into the dura mater defect. Commercially available medical fibrin glue and commercially available dura mater sealant are both operated using their original manufacturer's dedicated extended injection device; while the CNAS of Embodiment 1 of this invention completes the in-situ injection operation using an 18G puncture needle.

[0080] In actual endoscopic transnasal skull base surgery, dural defects are often highly inclined or even nearly vertical. Under the dual constraints of gravity and extremely confined surgical space, achieving stable and immediate interfacial retention of the sealing material has always been one of the core clinical challenges that urgently needs to be solved in this field. To evaluate the practical clinical translational potential of the hydrogel of this invention, this invention utilizes frozen human head cadaver specimens to establish a highly realistic clinical endoscopic transnasal surgical model (e.g., Figure 9 (as shown in a). After in situ injection, thanks to the rapid gelation characteristics of the physical network in the "fast / slow" dual-network mechanism of this invention, CNAS (corresponding to Figure 9 (b) The sealant precisely stays within the target defect area, without any gravity-driven flow or dispersion throughout the process, achieving precise spatial targeting and immediate sealing. In stark contrast, commercially available dura mater sealants (corresponding to...) Figure 9 c) and commercially available fibrin glue (corresponding to Figure 9In section d), both products exhibited significant downward migration and diffusion. Although these two products barely achieved coverage of the defect surface, this gravity-driven, uncontrollable displacement poses significant clinical risks. On the one hand, it significantly weakens the thickness of the effective sealing layer at the target defect site, increasing the likelihood of postoperative leakage; on the other hand, the randomly lost material can easily lead to accidental adhesions in non-target areas (such as surrounding healthy nerves and blood vessels), thereby causing serious surgical complications. In summary, the hydrogel of this invention successfully overcomes the technical bottlenecks of traditional injectable sealants, such as difficulty in positioning during complex laparoscopic procedures and susceptibility to gravity-induced loss, providing a highly efficient sealing solution for sealing skull base dural defects in clinical practice.

[0081] The above embodiments are merely examples. Those skilled in the art can adjust the specific composition and corresponding concentration of each solute in the two-component precursor solution for forming the injectable bioadhesive hydrogel, as well as the ratio of the two-component precursor solution, according to actual clinical conditions. For example: 1. Flexible adjustment of size and shape: The dura mater sealant obtained based on the present invention can be adjusted in situ according to the actual area of ​​the dura mater defect at the base of the skull, including the single injection volume, coverage thickness and final shape.

[0082] 2. Customized Control of Crosslinking Density: The polyethylene glycol derivatives used in this invention are not limited to the 10,000 Da molecular weight shown in the examples; other specifications such as 2,000 Da, 5,000 Da, or 20,000 Da can also be used. Since, at the same mass concentration, a smaller molecular weight results in a higher molar concentration of reactive functional groups within the system, leading to a higher degree of crosslinking, the mechanical strength of the hydrogel can be customized by flexibly combining polyethylene glycol derivatives of different molecular weights.

[0083] 3. Customized Regulation of In Vivo Degradation Cycle: This invention can adjust the degradation rate of the hydrogel by changing the type of polyethylene glycol active ester to match the repair cycle of different defects. The underlying mechanism is that the degradation of the covalent network mainly depends on the hydrolysis of ester bonds at the cross-linking nodes. Different types of active esters have different lengths of aliphatic carbon chains (methylene segments) near the ester bonds, which directly determines the local steric hindrance and hydrophobic shielding effect of the ester bonds. If an accelerated in vivo degradation rate is required, polyethylene glycol succinimide succinate (4-arm PEG-SS) can be used as an equivalent substitute. 4-arm PEG-SS has one less carbon atom than the polyethylene glycol succinimide glutarate (4-arm PEG-SG) in the examples, resulting in less steric hindrance that makes it easier for water molecules to attack the ester bonds, thus accelerating their breakage. Conversely, if a longer in vivo degradation time is required to provide a more durable sealing support, a derivative containing a longer carbon chain can be used as an equivalent substitute, such as polyethylene glycol succinimide propionate (4-arm PEG-SAP) or polyethylene glycol succinimide ester (4-arm PEG-SAZ). The longer carbon chain provides spatial crowding and localized hydrophobic enhancement, effectively resisting the intrusion of water molecules, thereby significantly slowing down the hydrolysis rate and extending the material's in vivo residence time.

[0084] In addition to calcium sulfate, other water-soluble calcium salts (such as calcium chloride, calcium carbonate, calcium lactate, calcium gluconate, and calcium hydrogen phosphate) can also be used for calcium salts; in addition to sodium alginate, other cation-corresponding alginates, oxidized alginates, methacrylamide alginates, and oxidized methacrylamide alginates can also be used for alginate components.

[0085] Those skilled in the art will readily understand that the above description is merely a preferred embodiment of the present invention and is not intended to limit the scope of protection of the present invention. The core mechanism of the present invention lies in utilizing the rapid physical cross-linking of alginate components and calcium salts, synergistically with the slow covalent cross-linking of polyethylene glycol components with different modifying groups, to construct a fast / slow dual-network system to achieve watertight sealing. Any non-substantial fine-tuning or equivalent substitution made based on the spirit and core cross-linking mechanism of the present invention regarding the specific types of each component (such as using other alginate derivatives or calcium salts with equivalent cross-linking activity), molecular weight, and concentration ratio of each component (e.g., scaling the concentration in accordance with conventional techniques to adapt to specific injection devices), as long as the final technical effect achieved is substantially the same as the minimally invasive injection, in-situ retention, and mechanical self-reinforcing properties of the hydrogel of the present invention, should fall within the scope of protection covered by the claims of the present invention.

Claims

1. A precursor for an injectable bioadhesive hydrogel used for endoscopic transnasal skull base dura mater sealing, characterized in that, The product includes a first solvent, a second solvent, alginate powder, calcium salt powder, amino-modified polyethylene glycol powder, and polyethylene glycol powder modified with active ester bonds; wherein the first solvent is deionized water and the second solvent is phosphate buffered saline (PBS). By mixing calcium salt powder with a first solvent to form a homogeneous solution containing calcium salt, mixing alginate powder with a second solvent to form a homogeneous solution containing alginate, and then mixing the homogeneous solution containing calcium salt with amino-modified polyethylene glycol powder to form a homogeneous first-component precursor solution, and finally mixing the homogeneous solution containing alginate with the polyethylene glycol powder modified with active ester bonds to form a homogeneous second-component precursor solution, the mixing of the first-component precursor solution and the second-component precursor solution can achieve the following: the alginate component and the calcium salt undergo rapid ionic cross-linking to form a first physical network, while the amino-modified polyethylene glycol component and the polyethylene glycol component modified with active ester bonds undergo slow covalent cross-linking to form a second chemical network. The first physical network and the second chemical network interpenetrate to form a dual-network system, which is an injectable and adhesive hydrogel.

2. A precursor for an injectable bioadhesive hydrogel used for endoscopic transnasal skull base dura mater sealing, characterized in that, include: The homogeneous solution containing calcium salts, the homogeneous solution containing alginate components, the polyethylene glycol powder with amino modification, and the polyethylene glycol powder with active ester bond modification; wherein the homogeneous solution containing calcium salts uses deionized water as a solvent, and the homogeneous solution containing alginate components uses phosphate buffered saline (PBS) as a solvent. By separately mixing the homogeneous solution containing calcium salt and the amino-modified polyethylene glycol powder to form a homogeneous first-component precursor solution, and then mixing the homogeneous solution containing alginate and the active ester-modified polyethylene glycol powder to form a homogeneous second-component precursor solution, and finally mixing the first-component precursor solution and the second-component precursor solution, the following can be achieved: the alginate component and the calcium salt undergo rapid ionic cross-linking to form a first physical network, while the amino-modified polyethylene glycol component and the active ester-modified polyethylene glycol component undergo slow covalent cross-linking to form a second chemical network. The first physical network and the second chemical network interpenetrate to form a dual-network system, which is an injectable and adhesive hydrogel.

3. A two-component precursor solution for an injectable bioadhesive hydrogel used for endoscopic transnasal skull base dura mater sealing, characterized in that, It includes a first component precursor solution and a second component precursor solution, wherein, The first component precursor solution is a homogeneous solution containing both calcium salt and amino-modified polyethylene glycol components. The second component precursor solution is a homogeneous solution containing both alginate components and polyethylene glycol components modified with active ester bonds. When the first component precursor solution and the second component precursor solution are mixed, the following can be achieved: the alginate component and the calcium salt undergo rapid ionic cross-linking to form a first physical network, while the amino-modified polyethylene glycol component and the active ester-modified polyethylene glycol component undergo slow covalent cross-linking to form a second chemical network. The first physical network and the second chemical network interpenetrate to form a dual-network system, which is an injectable and adhesive hydrogel.

4. The precursor as described in claim 1 or 2, or the two-component precursor solution as described in claim 3, characterized in that, The alginate component is selected from alginate and its derivatives, preferably from at least one of alginate, oxidized alginate, methacrylamide alginate, and oxidized methacrylamide alginate; The calcium salt is selected from at least one of calcium chloride, calcium sulfate, calcium carbonate, calcium lactate, calcium gluconate, and calcium hydrogen phosphate, preferably calcium sulfate or calcium carbonate.

5. The precursor as described in claim 1 or 2, or the two-component precursor solution as described in claim 3, characterized in that, The amino-modified polyethylene glycol components include at least one of linear, biarm, triarm, tetraarm, hexaarm, or octaarm polyethylene glycols containing an amino group (-NH2). Preferably, the molecular weight of the amino-modified polyethylene glycol component is in the range of 2,000 to 40,000 Da.

6. The precursor as described in claim 1 or 2, or the two-component precursor solution as described in claim 3, characterized in that, The polyethylene glycol components modified with active ester bonds include at least one of linear, biarmed, triarmed, tetraarmed, hexaarmed, or octaarmed polyethylene glycols containing N-hydroxysuccinimide (NHS) active end groups. Preferably, the active ester bond type includes one of succinimide glutarate (SG), succinimide succinate (SS), succinimide propionate (SAP), and succinimide azelate (SAZ); More preferably, the polyethylene glycol component modified with active ester bonds has a molecular weight range of 2,000 to 40,000 Da.

7. The precursor solution as described in claim 1 or 2, or the two-component precursor solution as described in claim 3, characterized in that, In the first component precursor solution: the mass ratio of calcium salt to solvent volume is 0.0005 g / mL ~ 0.005 g / mL, preferably 0.001 g / mL ~ 0.0015 g / mL; In the second component precursor solution, the mass ratio of alginate to solvent volume is 0.005 g / mL to 0.05 g / mL, preferably 0.01 g / mL to 0.015 g / mL; The amino-modified polyethylene glycol component contained in the first component precursor solution and the polyethylene glycol component with active ester bond modification contained in the second component precursor solution satisfy the following: the molar ratio of amino (-NH2) functional group to active ester bond (-NHS) functional group is 1:0.5 to 1:5, preferably 1:1.

5.

8. The method for preparing the two-component precursor solution according to any one of claims 3-7, characterized in that, Includes the following steps: Preparation steps of the first component precursor solution: Dissolve the amino-modified polyethylene glycol component powder in a pre-prepared calcium salt aqueous solution, mix evenly to obtain the first component precursor solution; Preparation steps of the second component precursor solution: Dissolve the polyethylene glycol component powder with active ester bond modification in pre-prepared phosphate buffer (PBS) containing alginate, and mix well to obtain the second component precursor solution.

9. The use of the precursor as described in claim 1 or 2, or the two-component precursor solution as described in any one of claims 3-7, in the preparation of dura mater sealants.

10. An injectable bioadhesive hydrogel for endoscopic transnasal skull base dura mater sealing, characterized in that, The hydrogel is obtained by rapidly injecting the two-component precursor solution as described in any one of claims 3-7 into the target defect area of ​​the dura mater at the base of the skull to be repaired, and then curing it in situ. It can be used as a dura mater sealant. The in-situ curing is carried out at 25℃~37℃; The first component precursor solution and the second component precursor solution are respectively placed in the two syringes of a double-barrel syringe, which is a Luer head connected syringe.